2014
DOI: 10.4314/ahs.v14i3.4
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal mortality in a referral hospital in Cameroon over a seven year period: trends, associated factors and causes.

Abstract: Background: The fourth Millennium Development Goals targets reduction of the mortality rate of under-fives by 2/3 by the year 2015. This reduction starts with that of neonatal mortality representing 40% of childhood mortality. In Cameroon neonatal mortality was 31% in 2011. Objectives: We assessed the trends, associated factors and causes of neonatal deaths at the Yaounde Gynaeco-Obstetric and Pediatric Hospital. Methods: The study was a retrospective chart review. Data was collected from the hospital records,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 10 publications
4
12
1
Order By: Relevance
“…The occurrence of neonatal death was higher in preterm’s than those born to term. Which consistent with studies [ 8 , 10 16 ]. This is due to the fact that being preterm exposes the new born for different conditions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The occurrence of neonatal death was higher in preterm’s than those born to term. Which consistent with studies [ 8 , 10 16 ]. This is due to the fact that being preterm exposes the new born for different conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Among the common diseases identified as a causes of neonatal mortality: pneumonia (5.13%), sepsis (9.68), congestive heart failure (33.33), jaundice (16.67), premature delivery (34.69) and other unidentified causes (9.84%). Which is consistent with studies [ 9 , 11 , 14 – 16 ] where the most common conditions for neonatal mortalities were preterm, asphyxia, neonatal infections; diarrhoea, sepsis, pneumonia, tetanus, and congenital malformations.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to our findings, a systematic review and meta-analysis conducted in East Africa found a prevalence of neonatal sepsis of 29.7% [25]. The prevalence of neonatal sepsis in the current study is lower than findings from Ethiopia at 45% [5], Tanzanian at [8], Cameroon at 37.9% [6] and Nigeria at 37.6% [7]. The difference in prevalence of neonatal sepsis could be explained by the difference in the clinical definition of sepsis at different settings.…”
Section: Discussionsupporting
confidence: 87%
“…Neonatal sepsis is highly prevalent in sub-Saharan African countries [4]. For example, the prevalence of neonatal sepsis is 45% in Ethiopia [5], 37.9% in Cameroon [6], 37.6% in Nigeria [7] and 34.1% in Tanzanian [8]. In Kenya, the prevalence of neonatal sepsis was reported at 29.3% [9].…”
Section: Introductionmentioning
confidence: 99%
“…Though high birth rates occur in sub-urban Cameroon where access to neonatal health services is inadequate [ 11 , 12 ], epidemiological data on neonatal mortality in this area remains scarce. Furthermore, the patterns of neonatal mortality are useful indicators of the quality of obstetrical and neonatal care in a particular setting, and their assessment ensures the estimation of the quality of health care [ 13 , 14 ]. Therefore, we proposed this study to determine the neonatal hospital mortality rate and its predictors in a sub-urban setting of Cameroon.…”
Section: Introductionmentioning
confidence: 99%